Resource Partitioning of Scots Pine (Pinus sylvestris L.) by Pine Shoot Beetles in Stands under Stress Conditions - Borkowski, Andrzej (Forests, 2021)
The pine shoot beetles Tomicus piniperda L. and T. minor Hartwig are sympatric species that occur on Scots pine in two habitats. Feeding by the beetles in tree crowns causes significant losses in tree growth and disturbs the crown’s proper development. A review of the subject literature showed that there had been no previous studies of interspecific competition in stands with different degrees of crown damage. The aim of this work was to assess the resource partitioning of stems by the two species in stands with damaged and undamaged crowns. Data were collected in the years 1992–2008 in stands containing Scots pine located at different distances from timber yards. A total of 259 natural traps were laid, and measurements of height and diameter at breast height were made for 900 pines. The surface area of each stem was divided into 20 equal sections by making a division lengthwise (into units) and laterally (into an upper and lower part). In total, 90,501 egg galleries of pine shoot beetles were counted on 9560 stem sections. Feeding by pine shoot beetles in the crowns of pines reduces site productivity and the nutritional suitability of stems. The results of niche segregation indicate pine shoot beetles exhibited spatial specialization in the use of resources. prefers the thicker part of the stem, and T. minor the thinner part. The population of T. piniperda on the trap logs was described using a multiple linear regression model with three explanatory variables. As a result of regression modelling, from the set of variables representing characteristics of habitats, trees and trap logs and the parameters of infestation, the following explanatory variables were selected: range of colonisation of a trap log (rc), site quality class (sqc), and crown undamaged (cu). The explanatory variables included in the MLRM model explain to a significant degree (p < 0.05) the niche breadth of T. piniperda on trap logs. In all validated plots, the mean real and model values for the niche of T. piniperda on the trap logs are similar (p > 0.5), confirming the high accuracy of the developed model.